2007
DOI: 10.3122/jabfm.2007.03.060064
|View full text |Cite
|
Sign up to set email alerts
|

Different Waist Circumferences, Different Metabolic Risks in Koreans

Abstract: Objective: We investigated the difference in metabolic parameters by waist circumference (WC) and body mass index (BMI) in a population of Korean men and women.Method: We collected data on 69,535 Korean men and women and performed a cross-sectional analysis of the data. Study subjects were grouped by BMI and WC. We measured metabolic parameters for each group and compared the differences in the metabolic abnormalities. Subjects were grouped as follows: normal group (NG; normal WC and normal BMI); centrally obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…Waist circumference (WC) increase is associated with increase of the risks of death [18,19], cardiovascular disease (CVD) [20,21], diabetes [19], metabolic syndrome [17,21,22], cancer [23], chronic respiratory disease [24,25], sleep apnea [16], and kidney stone formation [26]. Waist-to-height ratio (WHtR) increase is associated with increase of the risks of metabolic syndrome [22], CVD [20,21], and cancer [23]. Waist-to-hip ratio (WHR) increase is associated with increase of the risks of mortality [18], CVD [20], and cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…Waist circumference (WC) increase is associated with increase of the risks of death [18,19], cardiovascular disease (CVD) [20,21], diabetes [19], metabolic syndrome [17,21,22], cancer [23], chronic respiratory disease [24,25], sleep apnea [16], and kidney stone formation [26]. Waist-to-height ratio (WHtR) increase is associated with increase of the risks of metabolic syndrome [22], CVD [20,21], and cancer [23]. Waist-to-hip ratio (WHR) increase is associated with increase of the risks of mortality [18], CVD [20], and cancer [23].…”
Section: Introductionmentioning
confidence: 99%
“…(15) This finding was supported by evidence from clinical experience and epidemiological studies, wherein it was observed that there were many obese individuals who did not manifest the adverse phenotypic markers associated with increased cardiovascular mortality. (8) Over the years, studies have indicated the presence of a metabolically healthy obese phenotype in populations representing a variety of ages and ethnicities, among them adolescents, (16) the elderly, (17) Europeans, (18,19) Americans, (20) Africans, (21) Koreans, (22) Chinese (23) and Indians. (24) This theory also generated a great deal of popular interest, not only from the point of view of health economics (in which the existence of an obese state that does not require intervention, and thus allows for selective targeting of obesity had tremendous appeal), but also from patients'…”
Section: Discussionmentioning
confidence: 99%